Analisis Tata Kelola Bank Syariah, Leverage, Manajemen Laba dan Kinerja Keuangan - Tsarina Zenabia (Universitas Pamulang, 2021)
Corporate governance (CG) was still the first issue in predicted of behaviour of management and how are they managing their banking profits, while measurement of earnings using by modified Jones Models it was used to counting the value of accrual discretionary, and Return on Aset (ROA) as a proxied for financial performance. There are three structure models in this study, first models has proving that variable CG and Leverage had a significant effect on earning management the probability value of F statistic is shown at 0.000 < 0.05, adjusted R square value is 46.58%. The second model had found that variable CG and Leverage has a significant effect on financial performance, those probability value of F statistic shown at 0.008 < 0.05, adjusted R square value is 33.75%. Likewise, as the second model, the third model has shown that all independent variables have a significant effect on the dependent variable, and the probability value F statistic has proved at 0.012 < 0.05 and the adjusted R square value shown at 32.79%. During periods of research indicated that Sharia Islamic Banking has been doing earnings management by increasing or decreasing profits.